Van Hiele Model Applied to Descriptive Geometry to Strengthen Drawing (Docentes 2.0 Journal, 2021)
In the educational process, the presence of several actors is relevant; the teacher must teach the student to learn or meditate to acquire skills and abilities that allow them to be autonomous, positive, and constructivist through experiences, thus enhancing the complex process educational. The research objective was to analyze the contribution of the Van Hiele model applied to descriptive geometry for the strengthening of drawing through an interactive multimedia application (AMI) in students of the tenth grade of the Francisco de Paula Santander Normal School of the municipality of Malaga. For this purpose, it carried out the bibliographic review at the master's level at the international and national levels. The research paradigm was qualitative with an action research method. The implementation of this didactic unit began with a diagnostic test that allowed to establish the previous knowledge; later, five sessions were applied based on Van Hiele's theory to determine the students' progress during the process, ending with an exit test. It was followed by the collection of information and the analysis of the categories, concluding that the implementation of the didactic unit helped strengthen the concepts and develop skills related to drawing and spatiality in the students. It allowed these tools to be implemented in classrooms, not only in this subject but also in the others that make up the curriculum.
Keywords: Descriptive geometry; TBL; Van Hiele; didactic unit; teaching